Peningkatan Keterampilan Siswa SMK Melalui Pelatihan Perakitan Dan Pemrograman Robot Soccer Di SMKN 2 Wonogiri - siswoyo, agus; Artanto, Dian; Cahyono, Eko Aris Budi; Sutyasadi, Petrus (Lembaga Dongan Dosen, 2025)
This study aims to improve the skills of Vocational High School (SMK) students in the field of robotics through training in assembling and programming soccer robots. The training activities were carried out with a hands-on practice-based approach that included three main stages: delivering basic robotics theory, practicing assembling soccer robots using electronic components such as Arduino, and programming robots with Arduino IDE. The evaluation results showed a significant increase in student understanding, from an average of 50% before training to 85% after training. In addition, this training succeeded in increasing students' interest in robotics technology, training teamwork skills, and creating a collaborative and innovative learning environment. The obstacles found, such as limited training time and the need for intensive guidance for some students, could be overcome with additional assistance from instructors. This study provides an important contribution to the development of students' technological skills and supports the implementation of project-based learning in SMK.